The Road Less Traveled : A New Psychology of Love, Traditional Values, and Spiritual Growth - Peck, M. Scott (London Arrow Books, 1990)
Confronting and solving problems is a painful process which most of us attempt to avoid, yet avoidance can result in greater pain. Peck suggests ways of facing difficulties which can enable us to reach a higher level of self-understanding.
Keywords: Interpersonal relations -- Self-actualization (Psychology) -- Self-realisation